Social deprivation and prognostic benefits of cardiac surgery: observational study of 44 902 patients from five hospitals over 10 years. (2nd April 2009) - Pagano, D; Freemantle, N; Bridgewater, B; Howell, N; Ray, D; Jackson, M; Fabri, B M; Au, J; Keenan, D; Kirkup, B; Keogh, B E
Abstract : Objective To assess the effects of social deprivation on survival after cardiac surgery and to examine the influence of potentially modifiable risk factors. Design Analysis of prospectively collected data. Prognostic models used to examine the additional effect of social deprivation on the end points. Setting Birmingham and north west England. Participants 44 902 adults undergoing cardiac surgery, 1997-2007. Main outcome measures Social deprivation with census based 2001 Carstairs scores. All cause mortality in hospital and at mid-term follow-up. Results In hospital mortality for all cardiac procedures was 3.25% and mid-term follow-up (median 1887 days; range 1180-2725 days) mortality was 12.4%. Multivariable analysis identified social deprivation as an independent predictor of mid-term mortality (hazard ratio 1.024, 95% confidence interval 1.015 to 1.033; P<0.001). Smoking (P<0.001), body mass index (BMI, P<0.001), and diabetes (P<0.001) were associated with social deprivation. Smoking at time of surgery (1.294, 1.191 to 1.407, P<0.001) and diabetes (1.305, 1.217 to 1.399, P<0.001) were independent predictors of mid-term mortality. The relation between BMI and mid-term mortality was non-linear and risks were higher in the extremes of BMI (P<0.001). Adjustment for smoking, BMI, and diabetes reduced but did not eliminate the effects of social deprivation on mid-term mortality (1.017, 1.007 to 1.026, P<0.001). Conclusions Smoking, extremes of BMI, and diabetes, which are potentially modifiable risk factors associated with social deprivation, are responsible for a significant reduction in survival after surgery, but even after adjustment for these variables social deprivation remains a significant independent predictor of increased risk of mortality.